Evaluation of developer performance indicators in construction: models and productivity of the HR management system - Omelianenko , M. (Ways to Improve Construction Efficiency, 2023)
This article examines innovative approaches to HR management and their impact on the effectiveness of personnel management in modern organizations. It explores the conceptual foundations of human resource management, including the system approach, behavioral approach, and strategic approach. The author analyzes the latest technologies and practices such as the digitalization of HR processes, the use of artificial intelligence, and HR analytics, which optimize workforce management, improve employee engagement, and increase productivity. Modern technologies and practices for efficient company functioning include the integration of artificial intelligence, cloud computing, HR analytics, process automation, and the use of remote work platforms, which help optimize personnel management, enhance productivity and flexibility, reduce costs, and improve communication among employees. The application of agile working methods (Agile), robotic process automation (RPA), and talent development programs allows companies to adapt more quickly to changes in the business environment, enhancing competitiveness and ensuring sustainable development. The article highlights the role of these technologies as the foundation of innovative development for construction enterprises. Special attention is paid to the impact of information technologies on HR management in construction companies within the developer sector. The article analyzes current trends in personnel management development, particularly the implementation of digital tools to enhance the efficiency of human resource management, optimize teamwork, and attract highly qualified professionals. It emphasizes the importance of strategic HR management for improving company competitiveness in a rapidly changing business environment. Key indicators of successful HR strategies in construction developer projects under digital transformation conditions are identified. Furthermore, the article highlights the relationship between the effectiveness of HR strategies and the overall productivity of developer companies, especially in the context of large-scale construction projects. The importance of integrating analytics into HR processes to enhance company competitiveness is emphasized, and practical aspects of implementing HR analytics to improve management decisions in the field of construction development are discussed.